Mitral valve leaflet repair with the new PASCAL system: early real-world data from a German multicentre experience - Kriechbaum, Steffen D.; Boeder, Niklas F.; Gaede, Luise; Vigelius-Rauch, Ursula; Roth, Peter; Sander, Michael; Böning, Andreas; Bayer, Matthias; Elsässer, Albrecht; Möllmann, Helge; Hamm, Christian W.; Nef, Holger M.; et al. (Clinical Research in Cardiology, 2019)
Aims: To examine the clinical experience and practical use of the PASCAL transcatheter valve repair system (Edwards Lifesciences, Irvine, CA, USA) and to report some of the first clinical results. Methods and results: A total of 18 consecutive patients with severe, symptomatic mitral regurgitation (MR) were included in this German multicentre registry. All patients underwent clinical, echocardiographic, and laboratory assessment prior to the PASCAL procedure and before hospital discharge. MR was classified as functional in 6 patients, degenerative in 2, and combined in 10. All except one received a single PASCAL implant. The preprocedural severe MR present in all patients was reduced: grade 0 in 4 (22.2%), grade I in 11 (61.1%), grade II in 3 (16.7%). The v-wave was significantly reduced from 31.7 ± 9.5 to 18 ± 7.7 mmHg (p < 0.001). Independent leaflet capture, performed in 4 (22.2%) of the patients, wide clasps, and the 10-mm central spacer are features of the PASCAL device to optimize mitral leaflet repair. There were no periprocedural complications. Conclusion: PASCAL is a safe and effective mitral valve repair device for the treatment of severe MR. Device-specific features allow valve repair tailored to the individual anatomy of the underlying mitral pathology in each patient. Graphic abstract: [Figure not available: see fulltext.]
CRIS-Team Scopus Importer:2019-10-22
Keywords: Leaflet repair; Mitral regurgitation; Mitral valve disease; Mitral valve repair